2012
DOI: 10.1021/ic3011458
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Li-Based Metal–Organic Framework Tailored for the Selective Detection of Explosive Nitroaromatic Compounds: Direct Observation of Interaction Sites

Abstract: A luminescent lithium metal-organic framework (MOF) is constructed from the solvothermal reaction of Li(+) and a well-designed organic ligand, bis(4-carboxyphenyl)-N-methylamine (H(2)CPMA). A Li-based MOF can detect an explosive aromatic compound containing nitro groups as an explosophore, by showing a dramatic color change with concurrent luminescence quenching in the solid state. The detection sites are proven directly through single-crystal-to-single-crystal transformations, which show strong interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(77 citation statements)
references
References 33 publications
7
70
0
Order By: Relevance
“…[51][52][53][54][55][56][57][58][59] The intensity of the PL in 3 are largely dependent on the aromatics, exhibiting significant quenching behavior in the case of nitrobenzene, which may be related to the electron transfer from the electron-donating MOF to the highly electron-deficient nitrobenzene molecule upon excitation (Figure 4a). To examine sensitivity towards nitrobenzene in more detail, a batch of suspensions of 3 with gradually increasing nitrobenzene contents was prepared to monitor the emissive response ( Figure S7a).…”
Section: Luminescence Sensingmentioning
confidence: 99%
“…[51][52][53][54][55][56][57][58][59] The intensity of the PL in 3 are largely dependent on the aromatics, exhibiting significant quenching behavior in the case of nitrobenzene, which may be related to the electron transfer from the electron-donating MOF to the highly electron-deficient nitrobenzene molecule upon excitation (Figure 4a). To examine sensitivity towards nitrobenzene in more detail, a batch of suspensions of 3 with gradually increasing nitrobenzene contents was prepared to monitor the emissive response ( Figure S7a).…”
Section: Luminescence Sensingmentioning
confidence: 99%
“…MOFs with metal centers of europium, cadmium, zinc, lithium, iridium have been recently reported for the detection of nitro-aromatic explosives [22][23][24][25][26]. However, some of our tests on the nitro aromatic explosive sensing with MOFs revealed that, at times, it is difficult to obtain reproducible results in different sets of experiments.…”
Section: Introductionmentioning
confidence: 86%
“…However, in the process of building Li‐MOFs, it was found that some Li‐MOFs were not stable and easy to deliquesce in moist air because of the weaker coordination ability and fewer coordination number, which limited Li‐MOFs' application in gas adsorption. On the other hand, some Li‐MOFs have been explored the luminescent properties for sensing application . For example, Gao's group synthesized a series of Li‐based MOFs through the adoption the ortho‐hydroxyl arenedisulfonic acids, and suited the luminescent properties .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al used a π‐electron rich ligand to build a Li‐MOF, which showed the ability to detect Fe (III) ion and nitrobenzene . Kim et al reported a Li‐MOF constructed by a fluorescent ligand, bis(4‐carboxyphenyl)‐N‐methylamine, which can be used for luminescent sensing of nitrobenzene . However, the study on Li‐MOFs fluorescent sensors is still in its infancy, and worthy to explore …”
Section: Introductionmentioning
confidence: 99%